Distributed Secondary and Optimal Active Power Sharing Control for Islanded Microgrids With Communication Delays - Chen, Gang; Guo, Zhijun (IEEE transactions on smart grid, 2019)
As the communication delays in smart grid are considered, the novel secondary voltage and frequency restoration, the optimal active power sharing, and the accurate reactive power sharing protocols are proposed in this paper. The Lyapunov-Krasovskii functions are used to analyze the stability of our proposed distributed secondary control schemes. Sensitivity analysis of time delays is also provided. Whether the communication delays exist or not, the control protocols always guarantee that the output voltage amplitude and frequency of each distributed generator synchronize to the reference values and maintain the optimal active power sharing and the accurate reactive power sharing properties. Moreover, our proposed control protocols are implemented through sparse communication networks and thus meet the plug-and-play feature of the future smart grid. Simulation results are provided to show the effectiveness of the proposed control protocols.